Serviços de polinização em diferentes escalas espaciais: efeitos quantitativos e qualitativos na produção do café (coffea arabica l.) - Meireles, Desirée Ayume Lopes (2019)
About 70% of the most important agricultural crops depend on some extent of biotic pollination. However, anthropogenic actions have been modifying the environment and endangering the persistence of these organisms that promote pollination. The relationship of biotic pollination operating in increasing the productivity is described for many crops. Furthermore, the magnitude at which pollination can increase agricultural crop production can go beyond quantitative measures and may interfere with the chemical-physical properties of these crops, thus modifying the quality of these products. For coffee, this qualitative variation is very important for the final value of the product, since its price varies accordingly to its quality classification. For this reason, the objectives of this study were to verify the productivity increment in quantitative and qualitative parameters. The evaluated parameters were: the ratio of fruit set; the mean weight of the fruits and the composition of organic volatiles. To obtain these data, we selected 30 areas where pollinator exclusion experiments were performed in 5 individuals. In each individual, two branches were selected, the number of floral buds counted and one of them was bagged to prevent biotic pollination. At the end of the development period, the fruits were counted, weighed and submitted to processing to obtain the green coffee. The green coffee was toasted and volatile analysis was performed using GC-MS. We found the biotic pollination increased fruit yield when compared to the bagged branches, where only self-pollination and anemophilia were possible. Furthermore, there was an increase in the composition of volatiles in the comparison of these two treatments, where many functional chemical groups of organic volatiles linked to the quality were found in greater abundance in the branches exposed to biotic pollination. Still, the contribution of biotic pollination varies according to landscape characteristics. How to structure the landscape to obtain pollination, such as creating corridors between fragments and planting of cultivated areas with a greater perimeter relation, may be some measures taken to maximize the effectiveness of pollination.